Nivel de conocimiento sobre Diabetes Mellitus tipo 2 en pacientes diabéticos adultos y su asociación con la adherencia al tratamiento - Arista Montes, Alvaro Julio (2021)
To determine if there is an association between the level of knowledge about Diabetes Mellitus type 2 (DM2) and the adherence to treatment in adult diabetic patients. Material and methods: Cross-sectional descriptive study of cross-sectional association. A total of 110 diabetic patients attended in the outpatient clinic of the Regional Teaching Hospital of Trujillo were surveyed. The survey consisted of three parts: sociodemographic and disease data, knowledge about DM2 and adherence to treatment. The variables were analyzed using the Chi-square method with a significance level of 5%. Results: The mean age was 59.4 years. The female sex predominated in 72% and 33% had completed secondary education. Seventy-six percent of patients had SIS and 67% received treatment only with oral antidiabetic drugs. Sixty-six percent had at least one associated comorbidity, with a predominance of Arterial Hypertension. The mean HbA1c value was 7.5. In addition, 38% obtained an adequate level of knowledge of their disease and 41% considered themselves adherent to treatment, with a statistically significant association (p < 0.01). Conclusion: There is a statistically significant association between the level of knowledge about DM2 and adherence to treatment in adult diabetic patients.